Study of power dispatching control scheme in pyramid solar micro-grid - Bin-Juine Huang; Ming-Shian Chen; Zi-Ming Dong; Ming-Jia Lee; Wei-Hao Wu; Po-Chien Hsu (Energy Reports, 2020)
High penetration of solar PV systems will cause grid instability and requires storage and micro-grid. Pyramid solar micro-grid which consists of many solar home systems with storage was thus proposed. The reliability of solar micro-grid is an important issue. In the present study, we develop an advanced power dispatching control for pyramid solar micro-grid. A 4+4 solar micro-grid was built and tested. It is experimentally shown that the power dispatching control of the pyramid solar micro-grid using cascaded scheme is much reliable than the mobile-commander scheme. The data loss is near zero (0.002%).
Keywords: 330; Micro-grid; Solar micro-grid; Solar PV power